One-year neurodevelopmental outcome in children with asymptomatic congenital CMV infection - Maria Novelli; Elvira Caramuscio; Fabio Natale; Cristina Zitarelli; Rosa Ferri; Gianluca Terrin; Barbara Caravale (Elsevier, 2024)
Introduction: Infants with congenital CMV (cCMV) infection may show manifestations at birth and develop symptomatic disease, although the majority have no apparent clinical signs and should be considered asymptomatic (acCMV). Studies about neurodevelopmental and neurological sequelae in acCMV patients during childhood are few and contradictory, thus, the purpose of this study is to evaluate the neurological and neurodevelopmental outcomes in 1-year-old children with acCMV infections. Method: Thirty-five infants with acCMV infections were followed-up for 12 months and were compared to healthy children matched for age and gender. The Bayley Scales of Infant Development III (BSID-III) were administered, and neurological examinations were performed. Results: Children with acCMV infection showed minimal to mild neurological signs and the score obtained from the Motor Scale was significantly lower than that of the control group. No significant differences between the two groups were found regarding the Cognitive and Language Scales. Discussion: Asymptomatic congenital infection of CMV may be associated with a decrease in motor skills that may become evident during the first year of life. Close monitoring is essential to determine if rehabilitative treatment is required for children with asymptomatic congenital cytomegalovirus (acCMV). Longer follow-up is necessary to provide further details about their neurodevelopmental outcomes.